The Role of The Theological Means in The Identification of The West and The East - Ochilov Jamshid Abdurashidovich (Zien Journals, 2021)
This article examines the role of theological factors in the identification of western and eastern civilization, features of integration and the influence of globalization in the spiritual relations of the humanity
Keywords: Eastern and western civilization; integration; spiritual; cultural relations